Management Strategies for Iron Deficiency Anemia: A Clinical Review - Chaudhary, Hammad Tufail (Biological and Clinical Sciences Research Journal, 2025)
Iron deficiency anemia (IDA) is a prevalent hematological disorder with multifactorial etiology, including inadequate dietary intake, malabsorption, and chronic blood loss. Among these, gastrointestinal pathologies contribute significantly to the development and persistence of IDA, necessitating targeted clinical strategies for effective management. Objective: To review the current diagnostic and therapeutic approaches to IDA, with an emphasis on gastrointestinal-related causes and their specific management challenges and strategies. Methods: This review article synthesizes evidence from recent literature regarding the pathophysiology, diagnosis, and treatment of IDA in various gastrointestinal conditions. Databases including PubMed, MEDLINE, and EMBASE were searched for relevant studies published in the last 10 years. The clinical contexts explored include bariatric surgery, inflammatory bowel disease (IBD), portal hypertensive gastropathy, gastric antral vascular ectasia (GAVE), celiac disease, and small-bowel angioectasias. Particular focus is placed on the role of ferritin as a diagnostic marker and the comparative efficacy of oral versus intravenous iron therapy. Results: Ferritin remains the principal biomarker for diagnosing IDA, though interpretation must be adjusted in the presence of inflammatory conditions. Oral iron supplementation is the first-line therapy due to its accessibility and cost-effectiveness. However, gastrointestinal side effects and poor absorption often compromise its efficacy, particularly in patients with underlying gastrointestinal disorders. In such cases, intravenous iron formulations offer a superior alternative with improved patient outcomes. A multidisciplinary approach is often required to address the complex etiologies and optimize treatment plans. Conclusion: Effective management of IDA, particularly in the setting of gastrointestinal pathology, requires individualized treatment strategies guided by the underlying disease process, ferritin thresholds, and patient tolerance. Intravenous iron therapy is recommended for patients with impaired absorption or intolerance to oral formulations. Further research is essential to improve therapeutic options, reduce healthcare costs, and enhance the overall quality of life in patients affected by IDA.